`d/(dx)sin^-1(x)=1/sqrt(1-x^2)`

`F(theta)=sin^-1(sqrt(sin(theta)))`

`F'(theta)=(1/sqrt(1-sintheta)) * d/(d theta)sqrt(sintheta)`

`F'(theta)=(1/sqrt(1-sintheta)) *(1/2)(sintheta)^(-1/2) costheta`

`F'(theta)=costheta/((2sqrt(sintheta)sqrt(1-sintheta)))`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now